Facile synthesis of 3D plum candy-like ZnCo2O4 microspheres as a high-performance anode for lithium ion batteries. Issue 83 (23rd August 2016) - Fan, Binbin; Chen, Xiaohua; Hu, Aiping; Tang, Qunli; Fan, Haining; Liu, Zheng; Xiao, Kuikui
Abstract : We have demonstrated a facile method to prepared 3D plum candy-like ZnCo2 O4 microspheres using an ultrasonic spray pyrolysis technology. Abstract : In this paper, 3D plum candy-like ZnCo2 O4 microspheres (3D plum candy-like ZCO MSs) with nanoscale building blocks were synthesized by an ultrasonic spray pyrolysis technology and evaluated as anode materials for high-performance lithium ion batteries (LIBs). The uniform ZnCo2 O4 microspheres exhibit plum candy-like architectures and are built from a large amount of interconnected nanoparticles with a diameter of approximately 38 nm. Owing to the unique hierarchical porous structure, the 3D plum candy-like ZCO MSs exhibit many advantageous properties such as their ability to facilitate the transport of Li + and electrolytes by shortening the diffusion ways, to accommodate the mechanical stress and volume change associated with the Li + insertion/extraction processes, and to improve the contact area between electrode and electrolyte, which are beneficial to improve the electrochemical performance. As a consequence, the ZnCo2 O4 nanomaterials exhibit excellent cycling performance with a discharge capacity of 1030 mA h g −1 after 110 cycles at 200 mA g −1 and superior rate capability (769 mA h g −1 at 2000 mA g −1 ). In virtue of the simple synthesis method and excellent electrochemical performance, 3D porous ZCO MSs have huge potential as anode materials for the next-generation LIBs.